Anatomical Structure of Young Oil Palm (Elaeis guineensis Jacq.) Leaves for Callogenesis Initiation - Muhammad Ilham; Ernayunita Ernayunita (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Plant anatomy, a key area within biology, examines the structure and organization of plant organs and tissues. It underpins various disciplines such as physiology, ecology, taxonomy, and evolutionary biology. Anatomical data are typically obtained using the paraffin embedding, which facilitates detailed microscopic observations. In oil palm (Elaies guineensis Jacq.) tissue culture, young leaves are commonly used as explants in callogenesis inducing undifferentiated cell growth. The study aimed to describe anatomical characteristics of young oil palm leaves, analyze the correlation between anatomical traits across different leaf positions, and examine anatomical changes during callogenesis. Leaf samples were collected from positions -4, -5, -6, -7 and -8, processed using paraffin embedding technique, and analyzed microscopically. The percentages of callogenesis were also calculated for each leaf position. Data were analyzed using ANOVA, followed by Duncan’s Multiple Range Test (DMRT), and correlation analysis was performed in R Studio. The anatomical features included the adaxial and abaxial epidermis, cuticle, hypodermis, mesophyll (palisade and spongy parenchyma), vascular bundles (phloem and xylem), stomata, and sclerencyma. The correlations between mesophyll and leaf thickness were very strong (r= 0.97, p>0.05), indicating that as mesophyll tissue thickness increases, the overall leaf thickness also increases. Notably, leaves at position -8 exhibited the highest rate callogenesis, reaching 204%.